Unusual cutaneous toxicity after prolonged use of Hydroxyurea in polycythemia vera: a case report - Molinari, Elisa; Barabino, Gianfranco; Arboscello, Eleonora; Del Corso, Lisette; Bellodi, Andrea; Sicbaldi, Vera; Favorini, Serena; Ghio, Riccardo; Balleari, Enrico (Journal of Hematology and Oncology Research, 2015)
Hydroxyurea (HU) is commonly used for the long-term treatment of patients with chronic myeloproliferative neoplasms. The drug is usually well tolerated in the large majority of subjects, although systemic and/or localized toxicities have seldom been reported. Here we report a case of unusual cutaneous toxicity due long-term use of HU in a patient with polycythemia vera.
Keywords: Hydroxyurea; Polycythemia vera; myeloproliferative neoplasms; mucocutaneous toxicity